Temperature Dependence of Dark Spot Diameters in GaN and AlGaN. Issue 11 (6th September 2021) - Netzel, Carsten; Knauer, Arne; Brunner, Frank; Mogilatenko, Anna; Weyers, Markus
Abstract : Threading dislocations in c‐plane (Al, Ga)N layers are surrounded by areas with reduced light generation efficiency, called "dark spots." These areas are observable in luminescence measurements with spatial resolution in the submicrometer range. Dark spots reduce the internal quantum efficiency in single layers and light‐emitting devices. In cathodoluminescence measurements, the diameter of dark spots (full width at half maximum [FWHM]) is observed to be 200–250 nm for GaN. It decreases by 30–60% for Al x Ga1− x N with x ≈ 0.5. Furthermore, the dark spot diameter increases with increasing temperature from 83 to 300 K in AlGaN, whereas it decreases in GaN. Emission energy mappings around dark spots become less smooth and show sharper features on submicrometer scales at low temperature for AlGaN and, on the contrary, at high temperature for GaN. It is concluded that charge carrier localization dominates the temperature dependence of dark spot diameters and of the emission energy distribution around threading dislocations in AlGaN, whereas the temperature‐dependent excitation volume in cathodoluminescence and charge carrier diffusion limited by phonon scattering are the dominant effects in GaN. Consequently, with increasing temperature, nonradiative recombination related to threading dislocations extends to wider regions in AlGaN, whereas it becomes spatially limited in GaN. Abstract : Dark spot diameters around threading dislocations in c‐plane AlGaN are much smaller than in GaN and, contrary to GaN, increase with increasing temperature. These differences are caused by bandgap fluctuations and charge carrier localization on nanometer ranges in AlGaN. Localization allows excitonic recombination in AlGaN in spite of piezoelectric fields and bandgap gradients near dislocations.